2021
DOI: 10.1037/neu0000747
|View full text |Cite
|
Sign up to set email alerts
|

Detecting simulated versus bona fide traumatic brain injury using pupillometry.

Abstract: Objective: Pupil dilation patterns are outside of conscious control and provide information regarding neuropsychological processes related to deception, cognitive effort, and familiarity. This study examined the incremental utility of pupillometry on the Test of Memory Malingering (TOMM) in classifying individuals with verified traumatic brain injury (TBI), individuals simulating TBI, and healthy comparisons. Method: Participants were 177 adults across three groups: verified TBI (n = 53), feigned cognitive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…First, researchers are encouraged to further explore the integration of traditional CPT measures and eye-movement-based validity indicators (as long as the validity indicators do not overlap excessively, this may enhance their sensitivity; Sherman et al, 2020, p. 748). Second, additional eye-movement measures can be explored, including pupillometry (i.e., pupil size analyses) which showed potential when assessed during the performance of the test of memory malingering, TOMM, an established forced-choice memory-based PVT (Patrick et al, 2021). Third, sources of eye-movement patterns (i.e., intentional vs. unintentional effects) can be further explored through post-experimental debriefing surveys and other psychophysiological measures (e.g., use of pupil dilation as a marker of cognitive load; Patrick et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, researchers are encouraged to further explore the integration of traditional CPT measures and eye-movement-based validity indicators (as long as the validity indicators do not overlap excessively, this may enhance their sensitivity; Sherman et al, 2020, p. 748). Second, additional eye-movement measures can be explored, including pupillometry (i.e., pupil size analyses) which showed potential when assessed during the performance of the test of memory malingering, TOMM, an established forced-choice memory-based PVT (Patrick et al, 2021). Third, sources of eye-movement patterns (i.e., intentional vs. unintentional effects) can be further explored through post-experimental debriefing surveys and other psychophysiological measures (e.g., use of pupil dilation as a marker of cognitive load; Patrick et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, additional eye-movement measures can be explored, including pupillometry (i.e., pupil size analyses) which showed potential when assessed during the performance of the test of memory malingering, TOMM, an established forced-choice memory-based PVT (Patrick et al, 2021). Third, sources of eye-movement patterns (i.e., intentional vs. unintentional effects) can be further explored through post-experimental debriefing surveys and other psychophysiological measures (e.g., use of pupil dilation as a marker of cognitive load; Patrick et al, 2021). Finally, there is room to investigate the utility of the MOXO-dCPT in detecting feigned cognitive impairment in other neuropsychiatric disorders.…”
Section: Limitations and Venues For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…These tools extend beyond ophthalmology cabinets, finding applications in clinical and research settings. Key areas include emer gency departments for brain injury assessment [9][10][11][12], sports settings [13][14][15], for early detection of neuro-worsening [16][17][18], non-invasive monitoring of intracranial hyperten sion in critically ill brain trauma patients [19][20][21][22], post-cardiac-arrest evaluations o Traditionally, assessing pupils involved a pupil gauge for estimating size and a penlight or flashlight for manual evaluation of reactivity, categorized as "normal", "brisk", "slow", or "sluggish". In a recent study by Couret and colleagues, they found limited consistency between measurements of the pupil size obtained through an automated device compared to traditional clinical evaluation, revealing an overall disagreement rate of 18%.…”
Section: Pupillary Reflex Function Pupillary Light Reflexmentioning
confidence: 99%
“…These tools extend beyond ophthalmology cabinets, finding applications in clinical and research settings. Key areas include emergency departments for brain injury assessment [9][10][11][12], sports settings [13][14][15], for early detection of neuro-worsening [16][17][18], non-invasive monitoring of intracranial hypertension in critically ill brain trauma patients [19][20][21][22], post-cardiac-arrest evaluations of brainstem function [5,[23][24][25], and even in cases involving extracorporeal cardiopulmonary resuscitation [26]. Notably, during cardiopulmonary resuscitation (CPR), PLR serves as a surrogate method for monitoring CPR effectiveness and may predict the likelihood of returning to spontaneous circulation as evidenced in a cardiac arrest swine model [27].…”
Section: Pupillary Reflex Function Pupillary Light Reflexmentioning
confidence: 99%